Hot melt adhesive
By using β-1,3-glucan derivatives as the main component of hot melt adhesives, the environmental impact and resource limitations of petroleum-based resins are addressed, providing a highly sustainable hot melt adhesive with excellent adhesion, suitable for bonding and reusing wood-based materials.
Patent Information
- Application Number
- CN202480032727.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-17
- Filing Date
- 2024-05-13
- Publication Date
- 2025-12-12
AI Technical Summary
Existing hot melt adhesives mainly rely on petroleum-based resins, which have problems such as high environmental impact and limited resources. There is a need to develop alternative materials with high sustainability and excellent adhesion.
Using β-1,3-glucan derivatives as the main component, a hot melt adhesive with high pressure shear strength and excellent adhesion was prepared by substituting the hydroxyl groups of β-1,3-glucan with acyl groups. It is suitable for bonding wood-based materials.
It provides a highly sustainable hot melt adhesive with excellent adhesion and re-bonding properties, suitable for bonding plastics, metals, wood-based materials, etc., especially for the reuse of wood, reducing environmental impact and improving material sustainability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_6
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a hot melt adhesive. In addition, the present application relates to a method for producing a hot melt adhesive. BACKGROUND
[0002] Hot melt adhesives are adhesives that use a thermoplastic polymer which is solid at room temperature and liquid at high temperature, and utilize the cycle of heating-melting-cooling solidification to bond various materials such as plastics, metals, wood-based materials, paper, and painted surfaces. Hot melt adhesives are highly safe because they do not contain volatile solvents, and are widely used in industry because they have excellent properties such as not shrinking due to drying.
[0003] Hot melt adhesives generally use petroleum-based resins such as ethylene-vinyl acetate copolymer (EVA), olefin, synthetic rubber, polyamide, and polyester as raw materials. However, petroleum-based resins are environmentally burdensome, and are fossil resources that are likely to be depleted in the near future. Therefore, there is a demand for hot melt adhesives that use raw materials with high sustainability instead of petroleum-based resins.
[0004] In Patent Literature 1, an adhesive and an adhesive that use a by-product starch derivative as a raw material derived from a biomass resource of a natural origin are described. The adhesive and the adhesive are particularly useful in bonding or adhering plastic materials such as polyethylene terephthalate.
[0005] PRIOR ART DOCUMENTS PATENT LITERATURE Patent Literature 1: Japanese Patent Application Publication No. 2018-154723 SUMMARY
[0006] An object of the present application is to provide a hot melt adhesive that has high sustainability and excellent adhesion.
[0007] That is, according to the present application, the following mode is provided.
[0008] [1] A hot melt adhesive, wherein a β-1, 3-glucan derivative having the following formula (I): [Chemical Formula 1]
[0009] a β-1, 3-glucan derivative having the following formula (I): [In formula (I), R 1 is an acyl group represented by -COR 1 , R 1 is a hydrocarbon group, and n is a natural number of 1 or more. 1 ], a β-1, 3-glucan derivative having the following formula (I): The compressive shear adhesive strength under Condition 1 below was 1.0 N / mm 2 or more.
[0010] <Condition 1> A wood piece having a length of 30 mm, a width of 25 mm, and a thickness of 10 mm was used as an adherend.
[0011] Two pieces of the adherend were overlapped in the fiber direction with the hot melt adhesive having a length of 25 mm, a width of 25 mm, and a thickness of 0.1 mm interposed therebetween, and heat-pressed under a temperature of 190°C, a pressure of 1 MPa, and a time of 20 minutes, and then cooled to room temperature while maintaining the pressing pressure of 1 MPa, whereby the adherends were adhered to each other to produce a test piece.
[0012] The compressive shear adhesive strength (N / mm 2 ) of the test piece was measured in accordance with the compressive shear adhesive strength test method of the adhesive based on JIS K6852.
[0013] [2] The hot melt adhesive according to [1], wherein the softening temperature is 90°C or higher.
[0014] [3] The hot melt adhesive according to [1] or [2], wherein the 5% weight loss temperature is 250°C or higher.
[0015] [4] The hot melt adhesive according to any one of [1] to [3], wherein R 1 is a C5-C15 alkyl group.
[0016] [5] The hot melt adhesive according to any one of [1] to [4], wherein R 1 is a C5-C11 alkyl group.
[0017] [6] The hot melt adhesive according to any one of [1] to [5], wherein R 1 is a C5-C7 alkyl group.
[0018] [7] The acyl substitution degree of the β-1, 3-glucan derivative is 1.00 to 2.90.
[0019] [8] The hot melt adhesive according to any one of [1] to [7], wherein the compressive shear adhesive strength after re-adhesion under Condition 2 below is 1.0 N / mm 2 or more.
[0020] <Condition 2> The test piece was heated, the two pieces of the adherend were peeled, the adhered surfaces of the two pieces of the adherend peeled were overlapped again, and heat-pressing was performed at a temperature of 190°C, a pressure of 1 MPa, and a time of 20 minutes, and then the adhered surfaces were cooled to room temperature while maintaining the pressing pressure of 1 MPa, whereby re-adhesion was performed to produce a re-adhesion test piece.
[0021] With respect to the re-adhesion test piece, the pressure shear adhesion strength (N / mm 2 ) after re-adhesion was found in accordance with the pressure shear adhesion strength test method for adhesives based on JIS K6852.
[0022] [9] A method for producing the hot-melt adhesive according to any one of [1] to [8], which comprises substituting hydrogen of at least one hydroxyl group in at least one glucose unit of β-1, 3-glucan with -COR 1 (R 1 represents a hydrocarbon group). [9] A method for producing the hot-melt adhesive according to any one of [1] to [8],
[0023]
[10] A method for adhering the first adherend and the second adherend, comprising applying the hot-melt adhesive according to any one of [1] to [8] between the first adherend and the second adherend.
[0024]
[11] The method according to
[10] , wherein the first adherend and the second adherend are wood-based materials.
[0025]
[12] A method for adhering the first adherend and the second adherend, comprising: peeling the first adherend and the second adherend adhered in accordance with the method according to
[10] or
[11] by heating; and re-adhering the first adherend and the second adherend using the hot-melt adhesive remaining on the adhered surface of the first adherend and / or the adhered surface of the second adherend.
[0026]
[13] The hot-melt adhesive according to any one of [1] to [8], which is used for adhering wood-based materials.
[0027]
[14] Use of the hot-melt adhesive according to any one of [1] to [8] for adhering wood-based materials.
[0028] The present application can provide a hot-melt adhesive which is sustainable and has excellent adhesion. DETAILED DESCRIPTION
[0029] [TERMINOLOGY] "β-1,3-glucan" means a polysaccharide in which glucose is polymerized using β-1,3 bonds. The β-1,3-glucan can be derived from a living organism or can be a synthetic product. From the viewpoint of reducing environmental load, the β-1,3-glucan derived from a living organism is preferred, and the β-1,3-glucan derived from a plant is more preferred. In particular, from the viewpoint that the β-1,3-glucan is easily isolated and purified, the β-1,3-glucan isolated from a microalgae that synthesizes β-1,3-glucan in a cell is preferred. As the microalgae, Euglena (Japanese name: green worm) is preferred, and Euglena gracilis is more preferred. Euglena has the advantage that it is easy to cultivate and has a short growth cycle, and in addition, it accumulates a large amount of granules of β-1,3-glucan in a cell as a photosynthetic product. In addition, the isolation of β-1,3-glucan from the microalgae can be easily performed according to a conventional method. Note that the β-1,3-glucan produced by Euglena is also referred to as paramylum.
[0030] "β-1,3-glucan derivative" is typically a compound in which the hydrogen of at least one hydroxyl group in at least one glucose unit of β-1,3-glucan is replaced with a functional group such as an acyl group. The β-1,3-glucan derivative can be produced according to a conventional method. Specific examples of such a method will be described later.
[0031] "Adhesion" is the integration of the same or different substances or the state thereof. "Carrying out adhesion" is to form adhesion. "Adhesive" is a substance used for carrying out adhesion. "Adhesion" is a property of forming adhesion.
[0032] "Adhesion" is the integration of the same or different substances or the state thereof. "Carrying out adhesion" is to form adhesion. "Adhesive" is a substance used for carrying out adhesion. "Adhesion" is a property of forming adhesion.
[0033] "Hot melt adhesive" means an adhesive that uses a thermoplastic polymer that is in a solid state at ordinary temperature and in a liquid state at high temperature, and that uses the cycle of melting by heating and solidifying by cooling to bond various materials such as plastics, metals, wood-based materials, paper, and painted surfaces. The hot melt adhesive is highly safe because it does not contain a volatile solvent, and in addition, it has excellent properties such as not shrinking due to drying, and is therefore widely used in industry.
[0034] "Wood-based material" means a material that uses wood or bamboo. The wood can be any kind of wood of coniferous trees or broad-leaved trees. In addition, the wood-based material can be a material that is formed by processing wood or bamboo into a board shape, a small piece, or a fiber shape, such as plywood, particle board, or fiber board, or can be a recycled material thereof.
[0035] In this disclosure, the numerical ranges expressed using expressions such as "to" and "~" each include an upper limit and a lower limit, respectively. For example, the expression "A to B" or "A~B" using numerical values A and B means above A and below B. In addition, the expressions "A to B", "A~B" or "A and below B" independently include both "preferably above A" and "preferably below B".
[0036] Regarding the specific parameters in this disclosure, when multiple numerical ranges are described, any combination of upper and lower limits within the upper and lower limits of each numerical range can be used to form a preferred numerical range. Furthermore, the lower or upper limit of the numerical range described in this disclosure can be a value within that range, and can be replaced by the values shown in the embodiments.
[0037] In this disclosure, "and / or" includes both relational expressions represented by "and" and relational expressions represented by "or".
[0038] In this invention, "comprising" includes "mainly composed of," "substantially composed of," and "composed of." "Mainly composed of" includes "substantially composed of" and "composed of." "Substantially composed of" includes "composed of."
[0039] In this disclosure, objects referred to in the singular form, such as “a,” “an,” “the,” etc., are used, unless otherwise expressly indicated, including both the singular and plural forms of the object.
[0040]
Implementation Method
[0041] (Hot melt adhesive) In some embodiments, a hot melt adhesive is provided, comprising an adhesive having the following formula (I):
Chemical Formula 1
[0042] The structure represented is a β-1,3-glucan derivative. In formula (I), R 1 They are each independent of each other, using hydrogen or -COR. 1 The acyl group represented by R 1For hydrocarbon groups, n is a natural number, where it contains more than one -COR group. 1 】, The compressive-shear bond strength determined under condition 1 is 1.0 N / mm. 2 That's all. In other embodiments, a method for manufacturing the hot melt adhesive is provided.
[0043] <Condition 1> Use wood chips that are 30mm long, 25mm wide, and 10mm thick as the glued material.
[0044] Two pieces of the adhesive to be bonded are sandwiched between each other with a 25mm longitudinal, 25mm transverse and 0.1mm thick hot melt adhesive, aligned and overlapped in the fiber direction. They are then hot-pressed at 190°C, 1MPa pressure and 20 minutes, and then cooled to room temperature while maintaining a pressing pressure of 1MPa to bond them together and produce a test piece.
[0045] Regarding the test piece, the compressive-shear bond strength (N / mm²) was determined according to the JIS K 6852-based test method for adhesive compressive-shear bond strength. 2 ).
[0046] The hot melt adhesive in this embodiment can use biomass raw materials from natural sources such as Euglena, thus exhibiting high sustainability. Furthermore, this hot melt adhesive possesses excellent adhesion, suitable for bonding various materials such as plastics, metals, wood-based materials, paper, and coated surfaces, and is particularly suitable for bonding wood-based materials.
[0047] In this embodiment, the hot melt adhesive can be a hot melt adhesive used for bonding wood-based materials.
[0048] Even if the hot melt adhesive of this embodiment is composed only of β-1,3-glucan derivatives, it may further include other components as needed (plasticizers, antioxidants, ultraviolet absorbers, fillers, release agents, colorants, flame retardants, flame retardants and other additives, and other polymers other than β-1,3-glucan derivatives, etc.).
[0049] In one embodiment, the content of β-1,3-glucan derivative in the hot melt adhesive can be 50% by mass or more, 60% by mass or more, 80% by mass or more, 90% by mass or more, 98% by mass or more, or 100% by mass.
[0050] The hot melt adhesive in this embodiment is solid at room temperature and can be hot-pressed into a suitable shape. For example, when using the hot melt adhesive for the aforementioned compressive-shear bond strength, the hot melt adhesive is processed into a film with a length of 25 mm, a width of 25 mm, and a thickness of 0.1 mm.
[0051] In one embodiment, the hot melt adhesive may not be adhesive at room temperature. From the perspective that hot melt adhesives that are not adhesive at room temperature are easier to handle, hot melt adhesives that are adhesive at room temperature are more preferable.
[0052] (Compression-shear bond strength) In this embodiment, the compressive-shear bond strength can be 1.0 N / mm. 2 Above, 2.0 N / mm 2 Above, 3.0 N / mm 2 Above, 4.0 N / mm 2 Above, 5.0 N / mm 2 Above or 5.4 N / mm 2 That's all. Additionally, the compressive-shear bond strength can also be 1.0 N / mm. 2 Up to 9.0 N / mm 2 2.0 N / mm 2 Up to 9.0 N / mm 2 3.0 N / mm 2 Up to 9.0 N / mm 2 4.0 N / mm 2 Up to 9.0 N / mm 2 5.0 N / mm 2 Up to 9.0 N / mm 2 5.4 N / mm 2 Up to 9.0 N / mm 2 1.0 N / mm 2 Up to 5.4 N / mm 2 1.0 N / mm 2 Up to 5.0 N / mm 2 1.0 N / mm 2 Up to 4.0 N / mm 2 , and 2.0N / mm 2 Up to 4.0 N / mm 2 In addition, the compressive-shear bond strength can also be 1.3 N / mm. 2 2.3 N / mm 2 2.5N / mm 2 2.9 N / mm 2 3.6 N / mm 2 5.0 N / mm 2 5.5 N / mm 2 6.0 N / mm 2 6.2 N / mm 2 Or 8.6 N / mm 2This can be a range with these as upper or lower limits, or a range combining both upper and lower limits. Hot melt adhesives with these ranges of compressive-shear bond strength can achieve excellent adhesion. Furthermore, by setting a lower compressive-shear bond strength for applications requiring low adhesion and a higher compressive-shear bond strength for applications requiring high adhesion, it is possible to impart appropriate adhesion to the hot melt adhesive for the specific application.
[0053] The compressive-shear bond strength can be adjusted, for example, by adjusting the number of carbon atoms in the acyl group and the degree of acyl substitution of the β-1,3-glucan derivative described later. For example, in the case of -COR 1 R represents the acyl group 1 When the hydrocarbon group is C5 to C7 alkyl, adjusting the degree of acyl substitution from 1.50 to 2.90 can achieve a compressive-shear bond strength of 1.0 N / mm. 2 above.
[0054] It should be noted that β-1,3-glucan derivatives with a higher degree of acyl substitution generally have higher thermoplasticity. On the other hand, β-1,3-glucan derivatives with a lower degree of acyl substitution have higher hardness at room temperature. By adjusting the balance between thermoplasticity and hardness at room temperature, the compressive-shear bond strength can be increased (or decreased). For example, in the case of containing parastarch octanoate (i.e., as a -COR...), the bond strength can be increased (or decreased). 1 R represents the acyl group 1 When the hydrocarbon group is C7 alkyl, the compressive-shear bond strength is higher in the range of 1.70 to 2.80 acyl substitution degree. As another example, in the case containing parasitoid hexanoate (i.e., in the case where it is -COR...), the compressive-shear bond strength is higher. 1 R represents the acyl group 1 When the hydrocarbon group is C5 alkyl, the compressive shear bond strength is higher in the range of 1.90 to 2.90.
[0055] In the test pieces for the compressive-shear bond strength test of adhesives, the wood sheets used as the adherends are typically made of cedar, but are not limited to this. The adherends can be prepared by cutting rod-shaped boards with a width of 25 mm and a thickness of approximately 12 mm, the width and thickness being perpendicular to the fiber direction and longer in the fiber direction, planing them flat in the thickness direction to a thickness of 10 mm, and then continuously cutting them to a length of 30 mm in the fiber direction. In the test pieces, the adherends are aligned and overlapped in the fiber direction. Hot pressing can be performed using a commercially available hydraulic pressing device (e.g., the V-1815 multiaxial material testing machine, Sagamiya Manufacturing Co., Ltd.), according to the instructions accompanying the device. After hot pressing, the test pieces are typically left to stand at 20°C and 60% relative humidity for one week or longer before being used for the compressive-shear bond strength test of the adhesive.
[0056] The following is a summary of the test method for compressive-shear bond strength of adhesives based on JIS K 6852. One of the two adherends in the test specimen is fixed to a compression testing machine using a clamp. For the other adherend, a compressive load is applied in a direction parallel to the adhesive surface at 20°C and a test speed of 2 mm / min. The maximum load (N) at which the adhesive surface fails and the bond area (mm²) are then determined. 2 According to equation (1): Compression-shear bond strength (N / mm) 2 = Maximum load (N) / Bonding area (mm²) 2 ) (1) Calculate the compressive-shear bond strength (N / mm) 2 It should be noted that the bonding area (mm) 2 ( ) is the area of the bonding surface of the hot melt adhesive (25mm x 25mm = 625mm²) 2 ).
[0057] (β-1,3-glucan derivative) In the β-1,3-glucan derivative represented by the above formula (I), as a -COR 1 R represents the acyl group 1 The contained hydrocarbon groups are aliphatic or aromatic hydrocarbon groups. Aliphatic hydrocarbon groups can be straight-chain, branched, or have a cyclic structure. They can be saturated aliphatic hydrocarbon groups (alkyl) or unsaturated aliphatic hydrocarbon groups (alkenyl or alkynyl). As aliphatic hydrocarbon groups, their ease of synthesis, R... 1 Considering factors such as the degree of freedom, alkyl groups are preferred. Preferably, the alkyl groups are C5-C15 alkyl, C5-C13 alkyl, C5-C11 alkyl, C5-C9 alkyl, C5-C7 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, C9 alkyl, C10 alkyl, C11 alkyl, C12 alkyl, C13 alkyl, C14 alkyl, or C15 alkyl. Furthermore, these alkyl groups can be straight-chain, branched, or have a cyclic structure, but straight-chain is preferred. When the hydrocarbon group is an alkyl group with more carbon atoms, the distance between the acyl groups increases compared to alkyl groups with fewer carbon atoms, and the thermoplasticity of the β-1,3-glucan derivative tends to increase. However, when the hydrocarbon group is an alkyl group with too many carbon atoms, considering the potential increase in the interaction between the acyl groups, the thermoplasticity of the β-1,3-glucan derivative may sometimes decrease. By incorporating the aforementioned alkyl groups into the acyl groups, the intermolecular interactions of the β-1,3-glucan derivatives are appropriately adjusted, and hot melt adhesives with compressive-shear bond strengths within the aforementioned range can be readily obtained.
[0058] -COR 1 It can be acetyl, propionyl, isopropionyl, butyryl, isobutyryl, valeryl, hexanoyl, heptayl, octanoyl, nonanoyl, decanoyl, lauroyl, myristoyl, palmitoyl, stearyl, oleoyl, linoleoyl, linolenic acid, etc.
[0059] In formula (I), n is not particularly limited without prejudice to the scope of the invention, but is preferably 60 to 3000, more preferably 1000 to 2500, and even more preferably 1500 to 2000. As long as n is within the range described, a hot melt adhesive with moderate adhesiveness can be readily obtained.
[0060] The weight-average molecular weight (Mw) of the β-1,3-glucan derivative is more preferably from 300,000 to 600,000, and even more preferably from 400,000 to 500,000. The number-average molecular weight (Mn) of the β-1,3-glucan derivative is more preferably from 200,000 to 500,000, and even more preferably from 300,000 to 400,000. As long as the molecular weight of the β-1,3-glucan derivative is within the aforementioned range, a hot melt adhesive with moderate adhesiveness can be readily obtained.
[0061] The dispersion Mw / Mn of the β-1,3-glucan derivative is preferably 1.0 or higher and 1.6 or lower, more preferably 1.0 to 1.2. As long as the dispersion Mw / Mn is within this range, it is possible to produce a β-1,3-glucan derivative that better maintains the monodispersity of the β-1,3-glucan used as a raw material and is less prone to defects caused by melting point differences. Mw is the weight-average molecular weight, and Mn is the number-average molecular weight. Mw and Mn can be calculated using GPC (gel permeation chromatography) via polystyrene conversion.
[0062] The degree of acyl substitution of the β-1,3-glucan derivative is not particularly limited within the range that does not impair the effect of the present invention, but is preferably 1.00 to 2.90, more preferably 1.50 to 2.90, and even more preferably 1.70 to 2.90.
[0063] Furthermore, when the hydrocarbon group is a C5 or C6 alkyl group (i.e., the acyl group has 6 or 7 carbon atoms), the degree of acyl substitution of the β-1,3-glucan derivative is preferably 1.50 to 2.90, more preferably 1.70 to 2.90, and even more preferably 1.80 to 2.80. In applications where higher adhesion is required, a degree of substitution of 1.90 to 2.90 is preferred, more preferably 2.0 to 2.90, and even more preferably 2.10 to 2.80. When the hydrocarbon group is a C7 or C8 alkyl group (i.e., the acyl group has 8 or 9 carbon atoms), the degree of acyl substitution is preferably 1.50 to 2.90, more preferably 1.60 to 2.90, and even more preferably 1.80 to 2.90. In applications where higher adhesion is required, a degree of substitution of 1.70 to 2.80 is preferred, more preferably 1.70 to 2.40, and even more preferably 1.70 to 2.00. When the hydrocarbon group is a C9-C15 alkyl group (i.e., when the number of carbon atoms in the acyl group is 10 to 16), the degree of acyl substitution is preferably 1.50 to 2.60, more preferably 1.70 to 2.60, and even more preferably 1.90 to 2.50.
[0064] As mentioned above, β-1,3-glucan derivatives with higher acyl substitution degrees generally exhibit higher thermoplasticity. On the other hand, β-1,3-glucan derivatives with lower acyl substitution degrees tend to have higher hardness at room temperature. For hot melt adhesives to achieve excellent adhesion, it is important to balance appropriate thermoplasticity with appropriate hardness at room temperature; such hot melt adhesives tend to be readily available with acyl substitution degrees within the aforementioned range.
[0065] It should be noted that the degree of acyl substitution of β-1,3-glucan derivatives refers to the proportion of acyl groups bound to each glucose unit of the β-1,3-glucan from the starting material. For example, a degree of acyl substitution of 1.0 means that one substituent is introduced per glucose unit. Theoretically, the upper limit of the degree of acyl substitution is 3.0. The degree of acyl substitution can be evaluated using conventional methods. These methods include, for example, nuclear magnetic resonance spectroscopy (NMR) and elemental analysis. In the case of using nuclear magnetic resonance spectroscopy (NMR), typically, by... 1 H-NMR is used to evaluate the degree of acyl substitution based on the integral values of hydrogens directly bonded to the carbons of the glucose unit (hydrogens of the methylene and methine groups) and hydrogens of the acyl group.
[0066] The degree of acyl substitution based on the acyl group of the β-1,3-glucan derivative is adjusted in the β-1,3-glucan derivative manufacturing method described later by changing the addition ratio of the acylating agent to the glucose units contained in β-1,3-glucan.
[0067] The ratio of the acylating agent to the glucose units contained in β-1,3-glucan (acylating agent / glucan units contained in β-1,3-glucan (mol / mol)) is not particularly limited within a range that does not impair the effects of the present invention, but is preferably 6.0 to 1.0, more preferably 5.0 to 1.5, and even more preferably 4.0 to 2.0. Furthermore, the ratio of the acylating agent to the glucose units contained in β-1,3-glucan can be 2.5, 3.0, or 3.5, or these can be considered as upper or lower limits, or a combination of upper and lower limits.
[0068] By using acylating agents and glucose units contained in β-1,3-glucan at these ranges of addition ratios, the degree of acyl substitution of β-1,3-glucan derivatives based on acyl groups tends to be easily and appropriately adjusted.
[0069] (Method for manufacturing β-1,3-glucan derivatives) Methods for manufacturing β-as a 1,3-glucan derivative include synthetic methods that use fatty acids to acylate some or all of the hydroxyl groups in glucose that constitutes β-1,3-glucan.
[0070] Specifically, as shown in equation (2) below, a method can be described in which a solution of β-1,3-glucan is dissolved in a solvent, and in the presence of a base, a fatty acid chloride, a fatty acid anhydride, or a fatty acid ethylene compound is reacted sequentially as an acylating agent.
[0071] [Chemical Formula 2]
[0072] In this context, R is independently either hydrogen or acyl, at least a portion of R is an acyl, and n is a natural number.
[0073] Examples of fatty acid chlorides include acetyl chloride, butyroyl chloride, lauroyl chloride, myristoyl chloride, palmitoyl chloride, stearoyl chloride, hexadecenoyl chloride, oleoyl chloride, linoleoyl chloride, and linolenic acid chloride.
[0074] Examples of fatty acid anhydrides include acetic anhydride, propionic anhydride, and butyric anhydride.
[0075] Examples of ethylene compounds of fatty acids include vinyl acetate, vinyl propionate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl hexadecenoate, vinyl oleate, vinyl linoleate, and vinyl linolenic acid.
[0076] Examples of solvents include N,N-dimethylacetamide-lithium chloride mixed solvents, dimethyl sulfoxide, and 1,3-dimethyl-2-imidazolium ketone-lithium chloride solvents.
[0077] The base can be a known base such as pyridine, 4-dimethylaminopyridine, or triethylamine.
[0078] The reaction temperature, reaction time, and other conditions in this synthesis method shall be appropriately set by those skilled in the art, taking into account the type of acylating agent, the degree of acyl substitution, etc.
[0079] The obtained β-1,3-glucan derivatives can be processed into suitable shapes by hot pressing, for example. For example, using β-1,3-glucan derivatives as hot melt adhesives, in the case of the above-mentioned compressive-shear bond strength, they can be processed into films with a length of 25 mm, a width of 25 mm, and a thickness of 0.1 mm.
[0080] In one embodiment, the β-1,3-glucan derivative can be a film with a thickness of 0.01 mm to 1 mm.
[0081] (Softening temperature) In this embodiment, the softening temperature of the hot melt adhesive is not particularly limited as long as it does not impair the effects of the present invention, but it is preferably 90°C or higher, more preferably 100°C to 200°C, and even more preferably 110°C to 190°C. Furthermore, when the softening temperature is 90°C or higher, it can be 91.8°C, 115.5°C, 149.8°C, 161.4°C, 165.0°C, or 191.7°C, or these can be considered as upper or lower limits, or as a combination of upper and lower limits. With softening temperatures within these ranges, the hot melt adhesive tends to facilitate easier implementation of the heating-melting-cooling-curing cycle during bonding.
[0082] The softening temperature is the temperature at which fluidity increases rapidly and deformation begins during the process of raising the temperature. It can be measured using a thermomechanical analysis dynamic viscoelasticity measuring device (such as TMA / SS6000, Hitachi High Technology Scientific).
[0083] (5% temperature of weight loss) In this embodiment, the 5% weight loss temperature of the hot melt adhesive is not particularly limited without prejudice to the scope of the invention, but is preferably 250°C or higher, more preferably 270°C or higher. Furthermore, when the 5% weight loss temperature is 250°C or higher, it can be 274.8°C, 319.8°C, 322.8°C, 333.9°C, 342.6°C, or 347.3°C, or these can be considered as upper or lower limits, or as a combination of upper and lower limits. With a 5% weight loss temperature within these ranges, the hot melt adhesive exhibits less weight loss even when exposed to high temperatures, and tends to maintain adhesive strength.
[0084] "5% weight loss temperature" refers to the temperature at which a sample, based on its weight near room temperature, undergoes thermal decomposition and loses 5% of its weight when heated. This temperature can be measured using a differential thermal / thermogravimetric analysis device (e.g., Thermo plus EVO 2TG8120, Rigaku Corporation).
[0085] (Re-bonding compression-shear bond strength) In this embodiment, the compressive-shear bond strength of the hot melt adhesive after rebonding, determined under condition 2 below, can be 1.0 N / mm. 2 above.
[0086] <Condition 2> Prepare the test piece (a) obtained according to the method described in <Condition 1> above. That is, use a wood sheet with a length of 30 mm, a width of 25 mm, and a thickness of 10 mm as the bonding material. Place two of the bonding materials together with a 25 mm long, 25 mm wide, and 0.1 mm thick hot melt adhesive sandwiched between them, and perform hot pressing at a temperature of 190°C, a pressure of 1 MPa, and a time of 20 minutes to bond them together, thus preparing the test piece (a).
[0087] Heating the test piece (a), peeling off the two pieces of the adhered material, and making the adhesive surfaces of the peeled pieces of the adhered material overlap again, hot pressing is performed under the conditions of temperature 190°C, pressure 1MPa and time 20 minutes, thereby re-bonding to produce a re-bonded test piece (b).
[0088] Regarding the rebonded test piece (b), the compressive-shear bond strength (N / mm²) of the rebonded material was determined according to the compressive-shear bond strength test method for adhesives based on JIS K 6852. 2 ).
[0089] The process of heating the test piece to peel off the two adhered materials can be performed using conventional methods. For example, a small hot press (e.g., product name AH-2003, AS ONE) can be used, and the process can be performed by hand after heating at 160°C, 180°C, or 190°C for 30 minutes.
[0090] The re-bonded compressive-shear bond strength can be 1.0 N / mm. 2 Above, 2.0 N / mm 2 Above, 3.0 N / mm 2 Above, 4.0 N / mm 2 Above, 5.0 N / mm 2 Above, or 5.4 N / mm 2 That's all. Additionally, the compressive-shear bond strength after re-bonding can also be 1.0 N / mm. 2 Up to 9.0 N / mm 2 2.0 N / mm 2Up to 9.0 N / mm 2 3.0 N / mm 2 Up to 9.0 N / mm 2 4.0 N / mm 2 Up to 9.0 N / mm 2 5.0 N / mm 2 Up to 9.0 N / mm 2 5.4 N / mm 2 Up to 9.0 N / mm 2 1.0 N / mm 2 Up to 5.4 N / mm 2 1.0 N / mm 2 Up to 5.0 N / mm 2 1.0 N / mm 2 Up to 4.0 N / mm 2 or 2.0 N / mm 2 Up to 4.0 N / mm 2 Furthermore, the compressive-shear bond strength after re-bonding can be 3.1 N / mm. 2 5.2 N / mm 2 Or 5.4 N / mm 2 It can also be a range that uses these as upper or lower limits, or a range that combines upper and lower limits.
[0091] The rebonded compressive-shear bond strength is 1.0 N / mm. 2 The above-mentioned hot melt adhesives maintain excellent adhesion even during rebonding. Therefore, materials bonded with this hot melt adhesive do not require the application of new hot melt adhesive, even if the first bonded material is peeled off. Alternatively, the first-use hot melt adhesive can be removed and used directly and effectively for the second bond. Or, the need for additional hot melt adhesive can be reduced. This characteristic of hot melt adhesives is particularly useful when using them to process wood into houses and furniture, and the wood used in the houses and furniture after their service life is easily reused.
[0092] It should be noted that wood, when processed into houses, furniture, etc., is used for a long time, making it an excellent material from the perspective of carbon dioxide capture, utilization, and storage (CCUS). However, since most wood is incinerated after its use, the stored carbon dioxide is released back into the atmosphere. A powerful solution to avoid this is the reuse of wood. Here, reuse refers to the reuse of plywood, particleboard, fiberboard, etc., used in furniture and other products in other products. For wood reuse, it is often necessary to remove the bonded plywood, etc. As mentioned above, the hot-melt adhesive in this embodiment has excellent adhesion and can peel the wood off by heating, thus facilitating wood reuse and ensuring high sustainability.
[0093] (Manufacturing method of hot melt adhesive) In one embodiment, a method for manufacturing the above-mentioned hot melt adhesive is provided, comprising using -COR 1 (R) 1 β-1,3-glucan derivatives are prepared by substituting a hydrogen atom of at least one hydroxyl group in at least one glucose unit of β-1,3-glucan with a hydrocarbon group. This manufacturing method allows the use of biomass raw materials from natural sources such as Euglena, thus ensuring high sustainability. Furthermore, the hot-melt adhesives manufactured using this method exhibit excellent adhesion, making them particularly suitable for bonding wood. The method for preparing β-1,3-glucan derivatives is as described above.
[0094] (Adhesion method) In one embodiment, a method for bonding a first adherend and a second adherend is provided, the method comprising sandwiching the hot melt adhesive between the first adherend and the second adherend.
[0095] The first and second adhesives are not limited as long as they do not impair the effect of the present invention. However, when the first and second adhesives are wood, they can be well bonded together.
[0096] It should be noted that most conventional wood adhesives are synthetic adhesives that heavily rely on fossil resources such as formaldehyde. However, from the perspectives of limiting volatile organic compound (VOC) emissions, concerns about human health and the environment, and sustainability, the use of such synthetic adhesives is not preferred. In contrast, the method in this embodiment uses a hot-melt adhesive derived from biomass raw materials such as Euglena, which can be used from natural sources, thus having a lower burden on human health and the environment, and is highly sustainable.
[0097] The bonding method of this embodiment is not particularly limited as long as it does not impair the effect of the present invention. However, when the first and second adherends are wood, for example, after sandwiching a hot melt adhesive between the first and second adherends, the first and second adherends can be bonded by heating and pressing at a temperature of 90°C to 200°C and a pressure of 0.5 MPa to 10 MPa for 5 to 60 minutes and then cooling to room temperature.
[0098] (Re-bonding method) In one embodiment, a method for bonding a first adherend and a second adherend is provided, comprising: heating and peeling the first adherend and the second adherend, which are bonded together according to the method for bonding the first adherend and the second adherend; and re-bonding the first adherend and the second adherend using the hot melt adhesive remaining on the bonding surface of the first adherend and / or the bonding surface of the second adherend.
[0099] This method allows for the reuse of previously applied hot melt adhesives when reusing the adhered materials, thus making efficient use of resources. Furthermore, it reduces the time and effort required for reusing the adhered materials.
[0100] The method of heat peeling is not particularly limited as long as it does not impair the effect of the present invention. However, when the first and second adhered materials are wood, for example, peeling can be performed by heating the bonded first and second adhered materials at 90°C to 200°C for 5 to 60 minutes.
[0101] In one embodiment, the use of the above-mentioned hot melt adhesive in material bonding is provided.
[0102] The material can be any material within the range that achieves the effects of the present invention, but is preferably a wood-based material. The bonding of the material can be carried out in the same manner as the bonding method described above.
[0103]
Example
[0104] Synthesis of hot melt adhesives β-1,3-glucan derivatives include parastarch hexanoate (acyl carbon 6), parastarch heptaate (acyl carbon 7), parastarch octanoate (acyl carbon 8), parastarch decanoate (acyl carbon 10), parastarch laurate (acyl carbon 12), parastarch myristate (acyl carbon 14), and parastarch palmitate. Conventional methods can be illustrated by the following synthetic schemes.
[0105] [Chemical Formula 2]
[0106] In this context, R is independently either hydrogen or acyl, at least a portion of R is an acyl, and n is a natural number.
[0107] The synthesis method is described in more detail below using parastarch hexanoate with an acyl substitution degree of 2.12 as an example. 2.502 g of parastarch (15.431 mmol) was dispersed in 200 mL of pyridine, followed by the addition of 6.226 g (46.256 mmol) of hexanoyl chloride, and then stirred at 65 °C under a nitrogen atmosphere. Here, the ratio of acylating agent to glucose units contained in parastarch (acylating agent / glucose units contained in β-1,3-glucan (mol / mol)) was 3.0. After 3 hours, the homogeneous solution was added to 400 mL of water, yielding a pale yellow, viscous solid. This solid was removed by decantation and dispersed in 200 mL of methanol, stirred and washed (10 min, twice). Then, it was dispersed in 50 mL of chloroform and stirred at room temperature until homogenized. After homogenization, it was added to 300 mL of methanol, yielding a white gel. This operation was repeated twice. The target product (4.047 g, 10.972 mmol, degree of acyl substitution 2.12, yield 71.1%) was obtained by air drying (overnight) and subsequent vacuum heating (100 °C, 3 h).
[0108] Following the same synthetic method, the number of acyl carbons in the acylating agent and the ratio of the acylating agent to the glucose units contained in the parastarch were set as shown in Table 1 to obtain β-1,3-glucan derivatives. For example, using hexanoyl chloride as the acylating agent, and by setting the ratio of the acylating agent to the glucose units contained in the parastarch to be 3.5:1.0, parastarch hexanoate with a degree of acyl substitution of 2.76 was obtained. Furthermore, by using octanoyl chloride as the acylating agent and setting the ratio of the acylating agent to the glucose units contained in the parastarch to be 3.5:1.0, parastarch octanoate with a degree of acyl substitution of 2.87 was obtained.
[0109] The obtained β-1,3-glucan derivative was processed by hot pressing into sheets with a length of 25 mm, a width of 25 mm, and a thickness of 0.1 mm.
[0110] pass 1 H-NMR is used to evaluate the degree of acyl substitution based on the integral values of hydrogens directly bonded to the carbons of the glucose unit (hydrogens of the methylene and methine groups) and hydrogens of the acyl group.
[0111] Evaluation of softening temperature The softening temperature was evaluated using a thermomechanical analysis apparatus (TMA / SS6000, Hitachi High Technology Scientific).
[0112] [Evaluation of 5% temperature of weight loss] The 5% weight loss temperature was evaluated using a differential thermal / thermogravimetric synchronous measurement device (Thermo plus EVO 2 TG8120, Rigaku Corporation).
[0113] Evaluation of compressive-shear bond strength and post-rebonding compressive-shear bond strength. (Sample preparation) Cut rod-shaped boards, 25 mm wide and approximately 12 mm thick, with the width and thickness perpendicular to the fiber direction and longer in the fiber direction, from cedar wood planks. Plane the boards in the thickness direction to adjust the thickness to 10 mm. Cut these rod-shaped boards continuously in the fiber direction to lengths of 30 mm, thus preparing wood sheets. Align two sheets of the adhesive along the fiber direction, sandwich a 25 mm long, 25 mm wide, and 0.1 mm thick hot-melt adhesive between them, overlap the two sheets, and hot-press them at 190°C, 1 MPa, and 20 minutes. Then, cool to room temperature while maintaining a pressure of 1 MPa to bond them together, thus preparing test pieces. Hot-pressing is performed using a multiaxial material testing machine V-1815 (Saganomiya Seisakusho) according to the instructions accompanying the machine. After the test pieces are left to stand in an atmosphere at 20°C and 60% relative humidity for one week or longer, they are used for the compressive-shear bond strength test of the adhesive.
[0114] (Preparation of rebonded test pieces) The test piece prepared using the above method is heated to peel off the two adhered materials. The adhesive surfaces of the two peeled materials are aligned in the fiber direction and overlapped again. Under the above conditions, it is hot-pressed and cooled again, thereby re-bonding the two adhered materials to produce a re-bonded test piece. It should be noted that by using a small hot press (e.g., product name AH-2003, AS ONE), after heating at 160°C, 180°C, or 190°C for 30 minutes, the operation of peeling off the two adhered materials by hand is performed. After the re-bonded test piece is left to stand in an atmosphere at 20°C and 60% relative humidity for one week or longer, it is used for the compressive-shear bond strength test of the adhesive.
[0115] (Evaluation of compressive-shear bond strength) For the test pieces and rebonded test pieces, the compressive-shear bond strength was determined according to the test method for adhesive compressive-shear bond strength based on ISK6852. Specifically, one of the two adherends contained in the test piece or rebonded test piece was fixed in a compression testing machine (AUTOGRAPH AG-X plus precision universal testing machine, Shimadzu Corporation) using a clamp (wood shear test clamp, Shimadzu Corporation). For the other adherend, a compressive load was applied in a direction parallel to the bonding surface at 20°C and a test speed of 2 mm / min. The maximum load (N) at which the bonding surface failed and the bonding area (mm²) were then determined. 2 Based on equation (1): Compression-shear bond strength (N / mm) 2 = Maximum load (N) / Bonding area (mm²) 2 ) (1) Calculate the compressive-shear bond strength (N / mm) 2 For two test pieces or re-bonded test pieces, the compressive-shear bond strength is determined independently to two significant figures, and the average value is used for evaluation.
[0116] The results are shown in Table 1.
[0117] Table 1
[0118] In Table 1, the addition ratio (mol / mol) is the ratio of the acylating agent to the glucose units contained in β-1,3-glucan (acylating agent / glucan glucose units (mol / mol)). - indicates no data. X means that the test piece could not be peeled off in the above operation, and the re-bonded test piece could not be prepared.
[0119] As shown in Table 1, the hot melt adhesives of Examples 1 to 10 exhibit good compressive-shear bond strength and excellent adhesion compared to the hot melt adhesive of Comparative Example 1. In particular, the hot melt adhesives of Examples 1 to 6 are useful for applications requiring high adhesion due to their high compressive-shear bond strength, while the hot melt adhesives of Examples 7 to 10 are useful for applications requiring low adhesion due to their lower compressive-shear bond strength. Furthermore, the hot melt adhesives of Examples 5 to 7 also show good compressive-shear bond strength after re-bonding. Additionally, the hot melt adhesives of Examples 1 to 3 and Examples 5 to 7 are shown to have good softening temperature and 5% weight loss temperature.
[0120] The hot melt adhesives of Examples 1 to 10 do not exhibit adhesiveness at room temperature, making them easier to handle. On the other hand, the hot melt adhesive of Comparative Example 1 exhibits adhesiveness at room temperature.
[0121] It should be noted that all patents, patent applications, and publications cited in this disclosure are incorporated herein by reference.
[0122] [Industry Applicability] The hot melt adhesive of this invention is applicable to various materials used in bonding final or intermediate products in industrial manufacturing. Therefore, this invention has industrial applicability.
Claims
1. A hot melt adhesive, wherein, Including those with the following formula (I): 【Chemical Formula 1】 The structure represented is a β-1,3-glucan derivative. In equation (I), R 1 They are each independent of each other, using hydrogen or -COR. 1 The acyl group represented by R 1 For hydrocarbon groups, n is a natural number, where it contains more than one -COR group. 1 , The compressive-shear bond strength determined under condition 1 is 1.0 N / mm. 2 above, <Condition 1>: Use wood chips that are 30mm long, 25mm wide, and 10mm thick as the glue material. Two pieces of the aforementioned adhesive, sandwiched between them, are aligned and overlapped in the fiber direction with a 25mm longitudinal, 25mm transverse, and 0.1mm thick hot-melt adhesive. The mixture is then hot-pressed at 190°C, 1MPa, and for 20 minutes, followed by cooling to room temperature while maintaining a 1MPa pressing pressure. This process is then used to bond the materials and create a test piece. Regarding the test piece, the compressive-shear bond strength (N / mm) was determined according to the JIS K 6852-based test method for adhesive compressive-shear bond strength. 2 .
2. The hot melt adhesive according to claim 1, wherein, The softening temperature is above 90℃.
3. The hot melt adhesive according to claim 1 or 2, wherein, The 5% weight loss temperature is above 250℃.
4. The hot melt adhesive according to claim 1 or 2, wherein, R 1 It is a C5-C15 alkyl group.
5. The hot melt adhesive according to claim 1 or 2, wherein, R 1 It is a C5-C11 alkyl group.
6. The hot melt adhesive according to claim 1 or 2, wherein, R 1 It is a C5-C7 alkyl group.
7. The hot melt adhesive according to claim 1 or 2, wherein, The degree of acyl substitution of the β-1,3-glucan derivative is from 1.00 to 2.
90.
8. The hot melt adhesive according to claim 1 or 2, wherein, The compressive-shear bond strength after rebonding, calculated under condition 2, is 1.0 N / mm. 2 above, <Condition 2> The test piece is heated, and the two pieces of the adhesive are peeled off, allowing the adhesive surfaces of the peeled pieces to overlap again. Hot pressing is then performed at 190°C, 1 MPa, and 20 minutes. The piece is then cooled to room temperature while maintaining a pressure of 1 MPa, and re-bonded to create a re-bonded test piece. Regarding the rebonded test piece, the compressive-shear bond strength (N / mm) after rebonding was determined according to the JIS K 6852 method for testing the compressive-shear bond strength of adhesives. 2 .
9. A method for manufacturing the hot melt adhesive according to claim 1 or 2, wherein, Including the use of -COR 1 R replaces at least one hydrogen atom of at least one hydroxyl group in at least one glucose unit of β-1,3-glucan. 1 Representing a hydrocarbon group, β-1,3-glucan derivatives were prepared.
10. A method for bonding a first adherend and a second adherend, wherein, This includes applying the hot melt adhesive of claim 1 or 2 between the first adherend and the second adherend.
11. The method according to claim 10, wherein, The first and second adherends are wood-based materials.
12. A method for bonding a first adherend and a second adherend, wherein, include: The first and second adherends bonded together according to the method of claim 10 are then peeled off by heating. and The first and second adherends are re-bonded using the hot melt adhesive remaining on the adhesive surfaces of the first and / or the second adherends.
Citation Information
Patent Citations
Adhesive agent and sticky agent
JP2018154723A
